Extranodal NK/T cell lymphoma, nasal type: a rare diagnosis with common nasal presentation. Issue 6 (22nd June 2021) - Mohd Ramli, Siti Sarah; Husain, Salina; Wong, Yin Ping
Abstract : A 39-year-old man presented with bilateral nasal obstruction for 4 months and associated with hyposmia and foul-smelling nasal discharge. Nasal endoscopy showed irregular mucosa of the nasal cavity with easily bleeding. Nasal biopsy reported as extranodal Natural Killer/T cell lymphoma, nasal type. In-situ hybridisation for Epstein-Barr encoding region was positive. He was treated with six cycles of gemcitabine, oxaliplatin and L-asparaginase and peripheral blood stem cell transplant. After the treatment, he was asymptomatic until 9 months where he had splenic abscess and undergone splenectomy. He was asymptomatic of the disease for 2 years.